DETERMINAN PEMILIHAN METODE AKUNTANSI PERSEDIAAN PADA PERUSAHAAN TEKSTIL DAN GARMEN DI BEI (Periode 2017-2019) - Kirana Yuri Aprilia Maharani Dewi; Maslichah Maslichah; Dwiyani Sudaryanti (Universitas Islam Malang, 2021)
ABSTRACTThe research purpose to analyze the factors that work on the selection of inventory accounting methods at textile and garment companies listed on the Indonesia Stock Exchange. Firm variability, firm size, and current ratio are 3 independent variables that become element that work on the selection of accounting methods. While the inventory accounting methods (FIFO and average) is the dependent variable.The research sample used is textile and garment companies based on predetermined criteria (purposive sampling method). Through this purposive sampling method, a total of 8 textile and garment companies were listed on the Indonesia Stock Exchange for 3 periods from 2017 to 2019. The approach used in this study was quantitative with logistic regression analysis techniques.The test results using logistic regression from this study indicate that the 3 independent variables (company variability, company size and current ratio) significantly affect the selection of inventory accounting methods in textile and garment companies listed on the Indonesia Stock Exchange (IDX). Keywords : Firm Variability, Firm Size, Current Ratio, Inventory Accounting Methods